Muscular Power during a Lifting Task Increases after Three Months of Resistance Training in Overweight and Obese Individuals - Erika Zemková; Ol'ga Kyselovičová; Michal Jeleň; Zuzana Kováčiková; Gábor Ollé; Gabriela Štefániková; Tomáš Vilman; Miroslav Baláž; Timea Kurdiová; Jozef Ukropec; Barbara Ukropcová (MDPI AG, 2017)
Background: This study evaluates the effect on power produced during a modified lifting task in the overweight and obese after three months of either resistance or aerobic training. Methods: Seventeen male subjects divided randomly into two groups performed deadlift and deadlift high pull, both with increasing weights up to maximal power, prior to and after the training programs (three sessions per week). Results: Their mean power increased significantly during the deadlift at 20 kg (14.3%, p = 0.026), 30 kg (17.7%, p = 0.008), 40 kg (16.5%, p = 0.011), 50 kg (14.5%, p = 0.020), and 60 kg (14.3%, p = 0.021) and during the deadlift high pull at 30 kg (9.9%, p = 0.037), 40 kg (10.1%, p = 0.035), and 50 kg (8.2%, p = 0.044) after the resistance training. However, the group that participated in the aerobic training failed to show any significant changes in power performance during either the deadlift or deadlift high pull. Conclusion: Three months of resistance training enhances power outputs during a lifting task with weights from 30 to 50 kg (~40%-60% of 1-repetition maximum) in the overweight and obese. Because this test was sensitive in revealing pre-post training changes in lifting performance, it should be implemented in the functional diagnostics for overweight and obese individuals and also complement existing testing methods.